Expanding beyond carnivores to improve livestock protection and conservation - Rodriguez, Shari L.; Sampson, Christie (PLOS Biology, 2019)
This Perspective article highlights the fact that despite causing significant amounts of damage to livestock, noncarnivore species such as feral pigs and elephants are often excluded from the livestock protection conversation, potentially leading to missed opportunities to improve mitigation strategies.